Maze runner. The death cure The death cure - O'Brien, Dylan; Salazar, Rosa.; Scodelario, Kaya.; Esposito, Giancarlo; Sangster, Thomas; Darden, Dexter; Lee, Ki Hong. ([United States] : 20th Century Fox Home Entertainment, 2018)
In the epic finale to the saga, Thomas leads his group of escaped Gladers on their final and most dangerous mission yet. To save their friends, they must break into the legendary Last City, a WCKD-controlled labyrinth that may turn out to be the deadliest maze of all. Anyone who makes it out alive will get answers to the questions the Gladers have been asking since they first arrived in the maze.
Special features: Audio commentary by director Wes Ball, screenwriter T.S. Nowlin, producer Joe Hartwick,Jr.; The final run; Allies reunited.
Director, Wes Ball.
Dylan O'Brien, Rosa Salazar, Kaya Scodelario, Giancarlo Esposito, Thomas Sangster, Dexter Darden, Ki Hong Lee.
MPAA rating: PG-13.
DVD.
English, French, Spanish audio; French, Spanish subtitles.
Keywords: Action / Adventure; Suspense / Thriller; Sci-Fi.; Action